Extent of Early Clinical Response to Infliximab Predicts Long-term Treatment Success in Active Ulcerative Colitis. Issue 9 (September 2015) - Murthy, Sanjay K.; Greenberg, Gordon R.; Croitoru, Kenneth; Nguyen, Geoffrey C.; Silverberg, Mark S.; Steinhart, A. Hillary
Abstract : Background: The long-term effectiveness of infliximab (IFX) in ulcerative colitis (UC) and predictors of treatment response remain poorly characterized. Methods: A retrospective cohort study was conducted in 213 consecutive patients with active steroid-refractory or steroid-dependent UC treated with induction and scheduled maintenance IFX at an inflammatory bowel disease referral center. Outcomes included annual steroid-free remission (SFR), IFX failure with discontinuation, colectomy, and serious adverse events. Results: The 1- and 5-year cumulative probabilities for SFR were 39% and 14%, for IFX failure were 31.7% and 55.6%, and for colectomy were 19.2% and 37.4%, respectively. A sensitivity analysis considering the last clinical observation in patients with incomplete follow-up demonstrated a long-term SFR rate of 36%. Among responders to IFX induction therapy, achieving clinical remission before maintenance IFX therapy predicted SFR at 1 year (adjusted odds ratio = 4.50; 95% CI, 1.75–11.53), whereas the need for IFX dose intensification during the first year of therapy predicted a lower odds of SFR at 1 year (adjusted odds ratio = 0.28; 95% CI, 0.11–0.67) and a greater hazard of IFX failure beyond 1 year (adjusted hazard ratio = 2.57; 95% CI, 1.14–5.81). Older age and shorter UC duration at IFX initiation predicted poorer long-term outcomes. Conclusions: In patients with moderate-to-severe UC treated with scheduled IFX at an inflammatory bowel disease center, close to half of the patients are still on IFX at 5 years, although a smaller proportion of patients achieve long-term SFR. The magnitude and stability of early response to IFX is associated with long-term therapeutic benefit to this agent. Abstract : Article first published online 19 June 2015.Supplemental Digital Content is Available in the Text.